The Role of Olea Europaea L. Fruit on A2780, A172 and HFFF2 Proliferation: Olive activates c ell proliferation - Hadis Bahramiun; Maryam Noubarani; Mohammad Kamalinejad; Farshad H. Shirazi; Fatemeh Elahian; Fatemeh Balaghi; Fariborz Keyhanfar; Mohammad Reza Eskandari (Iranian Journal of Pharmaceutical Sciences, 2016)
Olea europaea L. commonly known as olive has been traditionally used for the prevention and treatment of many diseases since ancient times. Olive has been reported to possess a broad spectrum of pharmacological properties. In the present study, we investigated the activity of aqueous extract of Olea europaea L. fruit at various concentrations on A2780, A172, and HFFF2 cell lines proliferation by MTT assay. Aqueous extract of olive significantly increased cell proliferation in a dose dependent manner in the cell lines. It has been previously reported that olive has chemoproventive and anti-tumor effects. These disagreements can be explained by differences in cell line properties, type of olive and different solvents in the extracts. However, further investigation is needed to clarify the exact role of olive in cell proliferation and cancer. In this study fruit extract of Olea europaea L. showed more activatory effects on A2780 cell line in comparison with A172 and HFFF2. These differences in the activatory effects may be related to the activation of different signaling pathways in different cell lines.